Psychological foundation of education - Bhattacharya, Srinibas (New Delhi : Atlantic Publishers & Distributors (P) Ltd., 2008)
From the dawn of civilization, man has been marching in search of wisdom. Various experiments are projected through education, so that humanity, happiness and harmony be wedded together. Education is indispensable for making life and living meaningful and purposive. Its significance cannot be fully appreciated unless it is looked at in proper perspectives$1 (Bphilosophical, sociological and psychological. Psychology has a very significant bearing on education because of its influence on the various factors related to learning and teaching. The fundamental principles in psychology have tremendous impact on education and teaching. Without the knowledge of psychology a teacher is at a loss to understand the needs and problems in a child$1 (Bs life. Psychology provides the key to know the individual differences and meets them with appropriate educational programmes. It also helps the teachers to offer guidance and counselling to the pupils. In fact, psychology places education on a scientific basis and brings dignity to education as a discipline. The experimental approach has become feasible because of the contribution of psychology to education. Powers and propensities of mind have been analysed with the help of psychological techniques and measurement of mind has been a reality with the introduction of psychology as an objective science. Besides, it has been possible to mark out the different areas of mental operation. The mental process and the product, its structure and function have been discussed at length in the present book for bringing out the practical value of psychological approach. It is hoped that the present book will prove immensely useful for the students and teachers of both Education and Psychology. Even the general readers will find it highly informative.s
Includes bibliographical and references.
Keywords: Educational psychology